MORPHOLOGICAL AND HISTOMORPHOMETRIC CHARACTERISTICS OF THE THYROID GLAND OF WHITE OUTBREED RATS - Muattar Sh. Karimova; Shukhrat J. Teshaev (Central Asian Journal of Medicine, 2023)
Thyroid pathology is the second most common endocrinopathy after diabetes mellitus. The number of patients with temporary and permanent disabilities due to thyroid pathology is growing. Early diagnosis of morphological changes in pathologies of the thyroid gland and increasing the effectiveness of treatment are undoubtedly carried out with knowledge of the normal parameters of the thyroid gland. This article examines the morphological and histomorphometric characteristics of the thyroid gland of purebred rats.